Press Freedom with Press Accountability: Indonesian Experience - Andi Muhammad Asrun; Aditya Rahmadhony (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Freedom of the press is another side of press accountability. The press must obey the ethics of the press profession regulated by the press organization. Meanwhile, journalistic work is within the corridor of laws and regulations governing the press. On the one hand, the press works in the spirit of freedom, on the other hand, the press also demands accountability. This study shows that the Indonesian press was free after the end of the Soeharto Authoritarian Government. However, the gift of press freedom was also faced with various violations of the ethics of the press profession, which led to legal problems. The researcher used a normative legal research methodology. This study uses a normative research methodology. This study concludes that in addition to "freedom of the press", journalistic work is also required to obey the ethics of the journalistic profession regulated by the press organization.